1994
DOI: 10.1083/jcb.126.2.539
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface annexin II is a high affinity receptor for the alternatively spliced segment of tenascin-C.

Abstract: Abstract. We have investigated the binding of soluble tenascin-C (TN-C) to several cell lines using a radioligand binding assay. Specific binding was demonstrated to U-251MG human glioma cells and to a line of bovine aortic endothelial cells, but hamster fibroblasts showed no specific binding. Recombinant proteins corresponding to specific domains of TN-C were used to map the binding site(s) in TN-C. The alternatively spliced segment (TNfnA-D) inhibited the binding of native TN-C most strongly, and itself boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
145
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(149 citation statements)
references
References 59 publications
2
145
0
2
Order By: Relevance
“…With regard to the activity of the alternatively spliced domain of TN-C, two papers have appeared in the literature reporting an association with down-regulation of focal adhesion of cells (Murphy-Ullrich et al, 1991) and stimulation of corneal cell migration (Kaplony et al, 1991). Other studies using recombinant fragment of human TN-C have revealed that the alternatively Tenascin-C in lung cancer 101 spliced domain can bind to annexin II on human endothelial cells and promote cell migration (Chung and Erickson, 1994;Chung et al, 1996). These findings suggest that the larger TN-C molecules may be involved in detachment of cells from the stroma and in cell movement, thus affecting the malignant behaviour of tumour cells.…”
Section: Discussionmentioning
confidence: 96%
“…With regard to the activity of the alternatively spliced domain of TN-C, two papers have appeared in the literature reporting an association with down-regulation of focal adhesion of cells (Murphy-Ullrich et al, 1991) and stimulation of corneal cell migration (Kaplony et al, 1991). Other studies using recombinant fragment of human TN-C have revealed that the alternatively Tenascin-C in lung cancer 101 spliced domain can bind to annexin II on human endothelial cells and promote cell migration (Chung and Erickson, 1994;Chung et al, 1996). These findings suggest that the larger TN-C molecules may be involved in detachment of cells from the stroma and in cell movement, thus affecting the malignant behaviour of tumour cells.…”
Section: Discussionmentioning
confidence: 96%
“…RBA of Tenascin-C for binding PG binding sites ANX II was identified as a receptor protein for tenascin-C (TN-C) (Chung and Erickson, 1994). A splice variant fragment of TN-C, TNfnA-D, had the highest binding affinity for ANX II (Chung and Erickson, 1994).…”
Section: Identification Of Proteins In Band C By Seldi-tof-ms and Malmentioning
confidence: 99%
“…A splice variant fragment of TN-C, TNfnA-D, had the highest binding affinity for ANX II (Chung and Erickson, 1994). Annexin II binds progastrin P Singh et al Table 1.…”
Section: Identification Of Proteins In Band C By Seldi-tof-ms and Malmentioning
confidence: 99%
See 2 more Smart Citations